Experience capitalization: We found the process suited us - Allavi, Solomon Elorm (Technical Centre for Agricultural and Rural Cooperation, 2019)
For several years, we at Syecomp have been engaged in implementing projects – funded by national and international donors – and we have found that our key constraints have been documenting the impact of our work and sharing it effectively with the general public. When my colleagues and I heard about Experience Capitalization, we were very interested.